(untitled) (Journal of the College of Education for Women, 2019)
The importance of this topic may not be overlooked by many of the specialists, because it is one the sciences of the Arabic language, but it is an important method in the field of influencing the recipient and his aesthetic ability to create influential images as well.The talking about Semantic (Badi’iyah)is as old as the Arabic age, so it may be talking about it not the new thing because the people who specialized have preceded us and exhausted all the talk .